ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN KARTU PERDANA TELKOMSEL DI PEKANBARU - Anwar Saidy Siagian; Jushermi '; Henny Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect of simultaneous and partial brand equity on purchase decisions prime card Telkomsel in Pekanbaru. In this study consisted of five variables: the dependent variable. which is the Buying Decision and four free variables Brand Awareness, Brand Association, Perceived Quality and Brand Loyalty. The study was conducted with a sample of 100 people. Accidental studies using random sampling techniques by giving questionnaires to respondents. In terms of data analysis, research using qualitative methods and quantitative methods using SPSS (Statistical Package for Social Science) version 20.0. Brand Equity known significant effect simultaneously on Purchase Decision Prime Card Telkomsel in Pekanbaru. Simultaneous testing that proved of greater than. Also note Brand Equity significant effect partially to the Prime Card Purchase Decision Telkomsel in Pekanbaru of partial test results obtained have the brand equity value of t is greater than t table. The variables are the dominant influence on Prime Card Purchase Decision Telkomsel in Pekanbaru is variable Brand Loyalty. This it can be interpreted that the variable Brand Equity positive and significant effect on the purchase decision Prime Card Telkomsel in Pekanbaru. So to increase brand equity variables can improve the buying decision Prime Card Telkomsel in high Pekanbaru. Telkomsel brand equity value, it will increase the purchasing decisions of consumers against prime sympathy card.Keywords: Brand awareness, Brand association, Perceived Quality, Brand Loyalty, Purchase Decision.